Post Traumatic Stress Disorder Description in Victims of Natural Post Eruption of Merapi One Decade - Dwi Erna Wati; Mustikasari Mustikasari; Ria Utami Panjaitan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The eruption of Mount Merapi at the end of 2010 was recorded as the biggest eruption in the last 100 years. Survivors (survivors) can experience serious long-term psychological effects that have an influence on psychological well-being in carrying out daily activities. One of the symptoms most often found in victims of natural disasters is post-traumatic stress or Post Traumatic Stress Disorder (PTSD). The writing of this article is to find out the description of PTSD in victims of the natural disaster of the eruption of Mount Merapi for a decade. This type of descriptive qualitative research, with a population of adults (20-60 years) of 220 people who experienced post-eruption of Merapi in 2010, the sample according to inclusion criteria, namely dukuh and seven residents. Data collection is done by interview and observation. The results show that at this time the population / community is still showing signs and symptoms of PTSD which is feeling sad as if re-experiencing the eruption of Merapi in 2010, still feeling trauma (easily remembering the eruption of Mount Merapi when it did not want to remember it), anxiety when Merapi experienced increased activity and hopes that the Merapi eruption in 2010 will not happen again.